Dermatological Phototherapy and Photodiagnostic Methods - Krutmann, Jean (Springer, 2017)
New developments in the field of the commonly used photodiagnostic and phototherapeutic methods help to continuously improve the results in the daily practise. Edited by internationally renowned experts, the new edition offers up-to-date, comprehensive and clinically relevant information on every aspect of photodiagnostic and phototherapy. The book is structured in following parts:Photochemotherapy in daily practice, special phototherapeutic modalities and photoprotection in daily practice. Due to the detailed structure this new edition is even more reader-friendly and has a strong focus on clinical aspects. It includes: Guidelines for the treatment selections of specific diseases, practical guidelines for phototherapy with information about basic principles of photobiology, standardized test protocols for photodermatoses and diagnosis for skin tumors.